UPAYA GURU AKIDAH AKHLAK DALAM MENANGGULANGI DELINQUENCY SISWA KELAS VIII DI MTS AL MA’ARIF 02 SINGOSARI - Erika Faizatul Alfiah; Abdul Jalil; Ibnu Jazari (VICRATINA, 2019)
The formation of behavior is the main thing that needs to be done in improving the quality of the community and students in particular, but even though it has been held, these efforts have not been carried out optimally and their influence on the formation of good behavior. Thus causing juvenile delinquency in particular that has damaged moral values, teaching values, and undermined legal value. This research aims to find out how the efforts of moral akidah teachers in overcoming student delinquency at MTs Al-Maarif 02 Singosari. The research approach used by the author is a qualitative approach with a type of case study research. Data sources come from primary data and secondary data. data collection techniques by means of observation, interviews and documentation. From the results of research in the field it was found that the efforts of moral akidah teachers in overcoming student delinquency in the form of prevention efforts which included motivation and monitoring of social media, healing efforts included punishment, good emotional relationships between teachers and students, home visits, role models and Islamic activities.